Real-time distributed dispatch strategy for distribution transformer supply zone cluster based on cloud-edge collaboration architecture - Luo, Peng; Liang, Jifeng; Fan, Hui; Zeng, Siming; Yang, Guangjie; Lin, Junming (Frontiers in Energy Research, 2022)
Aiming at the problem of long-time scale prediction deviation in distribution network, a fast regulation strategy of cloud-edge coordination based on intelligent transformer supply zones edge consistency algorithm is proposed. The cloud makes the global initial optimal allocation to the edge transformer supply zone clusters, and then the cluster makes the secondary collaborative optimal allocation to the edge zones. A fast power interaction model within a cluster based on a consensus algorithm is established, and the micro incremental rate of dispatching cost is used as the consistency variable, so that the cluster adjustment amount is optimally allocated to each transformer supply zone, and the total dispatch cost of all transformer supply zones is minimized. The simulation example verifies the effectiveness of the cloud-edge collaborative fast control strategy based on the intelligent station cluster edge consensus algorithm in this paper.